Analysis of the Failure of the "Lamp Pocong" Lighting Project in Medan City: Lessons on Regional Planning in Medan City, North Sumatra - Sinelson Ndraha, Yason (Getpress Management Journals, 2024)
The project to install public street lighting in Medan City failed due to a number of challenges that hampered the compatibility between planning and implementation. Non-strategic placement, non-compliance with regulatory standards, and negligence in planning are the main problems faced. To answer this challenge, a problem formulation is proposed as to what caused the failure of the project to install public street lighting in the city of Medan. The aim of the research is to analyze the factors that caused the failure of the project and provide recommendations for future improvements. The method used is descriptive analysis based on data from literature study. The research results show that gaps between planning and implementation, coupled with a lack of consultation with communities, are the main causes of project failure. Closer collaboration between government and communities and careful monitoring during the project implementation phase are recommended to prevent similar failures in the future.